Prevalence and correlates of functional limitation among elderly in Kerala - Anjana, A.; Chacko, Asha T. (International research journal of management, IT and social sciences, 2014)
Performance of IADL could be closely related to biological variables such as age and sex. Since women outnumbered men among the sample population, it is hopeful to conclude that elderly women can be relished with functional independence, but in the advancement of their age, they have to suffer a lot. The results of the study showed that the extended life year is accompanied by increased demands on health care delivery systems as more part of life may be spent with some functional limitation. The prevalence of physical disability in elderly persons with functional limitation is, therefore, important for policy development in the care of the elderly. The most effective way to reduce the proportion of the population with disabilities is to delay the onset of disabilities. Living independently in familiar surroundings surely promotes a better aging and the development of living environments together with functional ability exert a profound influence on active aging. In Kerala situation, geriatric care should be focused on the necessities of elderly women since they have to live more years with functional limitation and disability than males. The number of people surviving into old age is increasing. The growth of the elderly population is expected to escalate in the coming years with respect to the general population. Longevity of people may result in poor health status, disability and loss of functional health. Information on disability is very important in responding to the care of the elderly.